Effect of Variation Conditions of The Extraction Process of Morinda Citrifolia L Leaves Using Ultrasound-Assisted Extraction Method (Uae) - Buanasari, Buanasari; Dhamayanti, Sonia Murniana Sri; Suryaningsih, Suryaningsih (Journal of Science and Technology Research for Pharmacy, 2021)
Background: Morinda citrifolia L. is widely used as traditional medicine for various diseases. The benefits of noni are studied from the seeds, fruit, leaves and root bark. This leaf active compound is rich in flavonoids, so an effective extraction process is needed to extract it. Conventional extraction generally takes a long time and involves a thermal process that can damage the compound, so it requires extraction with the latest methods, one of which is the use of ultrasonic waves. Aim: This study aims to examine the effect of variations in extraction process conditions on present yield, DPPH scavenging activity, flavonoid content and phenol content of Morinda citrifolia L leaves by varying the solids-solvent ratio (1:10, 1:20, 1:30, dan 1:40 g/mL), and extraction temperature (25, 35, 45, and 55ºC). Method: The process uses the ultrasonic assisted extraction method with 50 %V ethanol for 60 minutes. Result: The highest yield was obtained in the extraction with a solids-solvent ratio of 1:40 g/mL, at an extraction temperature of 55ºC, which was 32.29±0.066%. The highest flavonoid content (173.41±0.615 mg quercetin equivalent/g extract), phenol content (197.00±0.148 mg gallic acid equivalents/g extract) and DPPH scavenging activity (97.65±0.912%) was obtained in the extraction with a solids-solvent ratio of 1:30 g/mL, at an extraction temperature of 25ºC. The best extract measured antioxidant activity and IC50 values obtained with 23.21 µg/mL. Conclusion: The use of the ultrasonic assisted extraction method by selecting the optimal operating conditions greatly increases the amount of active compound uptake required.